2015
DOI: 10.1117/1.jbo.20.7.076006
|View full text |Cite
|
Sign up to set email alerts
|

Ballistic imaging of biological media with collimated illumination and focal plane detection

Abstract: A simple, affordable method for imaging through biological tissue is investigated. The method consists of (1) imaging with a wavelength that has a relatively small scattering coefficient (1310 nm in this case) and (2) collimated illumination together with (3) focal plane detection to enhance the detection of the ballistic photons relative to the diffusive light. We demonstrate ballistic detection of an object immersed in a 1-cm-thick cuvette filled with 4% Intralipid, which is equivalent to ∼1 to 2 cm of skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…This model was shown to predict the experimental results, 19,20,34 however, it was shown that there is a discrepancy of a factor of 2 to 4 in the prefactor of the diffusive term.…”
Section: Theoretical Modelmentioning
confidence: 92%
See 1 more Smart Citation
“…This model was shown to predict the experimental results, 19,20,34 however, it was shown that there is a discrepancy of a factor of 2 to 4 in the prefactor of the diffusive term.…”
Section: Theoretical Modelmentioning
confidence: 92%
“…However, experiments and simulations show disagreement regarding this point. 34 The mathematical model that was utilized in Ref. [15][16][17][18] Recent experiments reveal that the transition length depends not only on the scattering coefficient but on the collecting angle as well.…”
Section: Introductionmentioning
confidence: 99%
“…Photons travelling in scattering media can be divided into three broad categories [1][2][3]: ballistic photons, where there is no interaction with the medium and the photons propagate straight through with a coherent wavefront; snake photons which are weakly scattered, arrive immediately after ballistic photons and maintain some coherence since there are only minor deviations in direction; and diffuse photons which have scattered many times and have a trajectory that no longer corresponds to their initial propagation direction, leading to an incoherent wavefront. Ballistic and snake photons find many uses for imaging through scattering media [1,[4][5][6][7][8]. However, they are exponentially suppressed as the propagation depth increases.…”
Section: Introductionmentioning
confidence: 99%
“…Photons travelling in scattering media can be divided into three broad categories [1][2][3][4]: ballistic photons, where there is no interaction with the medium and the photons propagate straight through with a coherent wavefront; snake photons which undergo a few scattering events; and diffuse photons which have scattered many times and have a trajectory that no longer corresponds to their initial propagation direction, leading to an incoherent wavefront. Ballistic and snake photons find many uses for imaging through scattering media [2,[5][6][7][8][9]. However, ballistic photons are exponentially suppressed as the propagation depth increases.…”
Section: Introductionmentioning
confidence: 99%